Implementing lean six sigma throughout the supply chain : the comprehensive and transparent case study - Cudney, Elizabeth A.; Kestle, Rodney (Productivity Press, 2010)
Provides a comprehensive lean six sigma case study. This book follows a team as they implement a lean six sigma project and provides over illustrative 100 figures and tables. It presents the data, which are also included in the accompanying CD, and comprehensively explains how the team drew their conclusions